Effect of Operating Parameters on the Properties of Carbon Dots from Spent Coffee Grounds - Wareing, Thomas; Phan, Anh; Gentile, Piergiorgio; Cucinotta, Fabio (Journal of Technical Education Science, 2023)
Carbon dots (nanosized materials) exhibit excellent properties such as strong fluorescence, low cytotoxicity, biocompatibility, and good biodegradability which can be synthesized from various carbon sources such as biomass and food waste etc. Due to their unique properties, they are considered as potential alternatives to replace conventional metal-based quantum dots in a number of applications from energy storage, biomedicine to water treatment. In this work, we demonstrate an intensified and green approach to synthesize carbon dots from waste coffee. The synthesized carbon dots have application in sensing e.g. detecting heavy metals, contaminants in water, drug delivery and bioimaging.